Discursive syntax as part of applied linguistics - Kostrova, Olga (Glottodidactica, 2021)
In contemporary academia, there are no mono-semantic definitions of either applied linguistics or discursive syntax. I analyse how applied linguistics is understood in Russia, Poland and Germany, and present syntax as a part of applied intercultural linguistics. The analysed data are reflective texts by Russian and German participants of the intercultural project “Rilke and Russia” that took place in 2019, in Samara. I consider these texts for reflective discourse appearing as a result of speech acts realised as self-talk. In my analyses, I use methods that are specific for speech acts research on the one hand, and that are typical of syntax on the other. So, I identify the role subjects, their intentionality and the persons addressed. Then, I compare the syntactic means used by Russian and German role subjects and show that these means are influenced by national culture and mentality.